2022
DOI: 10.1017/s0007114522003166
|View full text |Cite
|
Sign up to set email alerts
|

Duyun compound green tea extracts regulate bile acid metabolism on mice induced by high-fat diet

Abstract: Duyun compound green tea (DCGT) is a healthy beverage with lipid-lowering effect commonly consumed by local people, but its mechanism is not very clear. We evaluated the effect of DCGT treatment on bile acids metabolism of mice with high-fat diet (HFD) - induced hyperlipidemia by biochemical indexes and metabolomics, and preliminarily determined the potential biomarkers and metabolic pathways of hyperlipidemia mice treated with DCGT as well as investigated its lipid-lowering mechanism. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, previous studies have shown that EGCG can bind to bile acids and alter the structure of mixed micelles composed of bile salts, phospholipids, and cholesterol, thereby reducing cholesterol solubility and potentially impacting lipid absorption. These findings provide insights into how EGCG-bile salt interactions may influence the bioavailability and cellular uptake of EGCG, as well as its effects on lipid metabolism [ 50 , 51 ]. These in vitro results suggest encapsulation of EGCG in WPI- and NaCas-stabilized emulsions can improve its intestinal absorption and bioavailability when administered orally [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies have shown that EGCG can bind to bile acids and alter the structure of mixed micelles composed of bile salts, phospholipids, and cholesterol, thereby reducing cholesterol solubility and potentially impacting lipid absorption. These findings provide insights into how EGCG-bile salt interactions may influence the bioavailability and cellular uptake of EGCG, as well as its effects on lipid metabolism [ 50 , 51 ]. These in vitro results suggest encapsulation of EGCG in WPI- and NaCas-stabilized emulsions can improve its intestinal absorption and bioavailability when administered orally [ 48 ].…”
Section: Resultsmentioning
confidence: 99%